2006
DOI: 10.1111/j.1528-1167.2006.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acceptance and Commitment Therapy for Drug Refractory Epilepsy: A Randomized Controlled Trial in South Africa—A Pilot Study

Abstract: Summary:Purpose: Psychological interventions in the treatment of epilepsy have been developed and evaluated for many years but the amount of research has hardly made an impact on how epilepsy is treated. The purpose of this study was to develop and evaluate a psychological treatment program consisting of acceptance and commitment therapy (ACT) together with some behavioral seizure control technology shown to be successful in earlier research.Methods: The method consisted of a randomized controlled trial group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 21 publications
(21 reference statements)
3
142
1
3
Order By: Relevance
“…Closer examination of the changes in seizure frequency showed that although 37.2% of patients reported a more than 50% reduction in seizure frequency, there were more patients (39.5%) who experienced a smaller than 50% improvement or no change at all. This finding is in contrast with the findings of the studies by Lundgren et al [43,44] who reported a significant decrease in seizure frequency as a result of ACT psychotherapeutic treatment. However, the overall evidence for effectiveness of psychological interventions for reducing seizures is mixed [11], and it is important to emphasise that the focus of the therapeutic approach used in our study was on the psychosocial issues associated with epilepsy rather than reduction of seizure frequency per se.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Closer examination of the changes in seizure frequency showed that although 37.2% of patients reported a more than 50% reduction in seizure frequency, there were more patients (39.5%) who experienced a smaller than 50% improvement or no change at all. This finding is in contrast with the findings of the studies by Lundgren et al [43,44] who reported a significant decrease in seizure frequency as a result of ACT psychotherapeutic treatment. However, the overall evidence for effectiveness of psychological interventions for reducing seizures is mixed [11], and it is important to emphasise that the focus of the therapeutic approach used in our study was on the psychosocial issues associated with epilepsy rather than reduction of seizure frequency per se.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is concordant with existing evidence from a small number of controlled studies of cognitive behavioural therapy and ACT for epilepsy. Martinovic et al reported both significant reduction of depressive symptoms and improved quality of life in adolescent patients receiving a CBT intervention, compared to a control group [41], a CBT intervention was also effective in improving quality of life in a small RCT from Hong Kong [42], and two small-scale RCTs by Lundgren et al showed significant improvements in quality of life following a short-term ACT treatment [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Bohlmeijer, Prenger, Taal, & Cuijpers, 2010;Dahl, Wilson, & Nilsson, 2004;Fitzpatrick, Simpson, & Smith, 2010). Interventions have focused on adjustment to illnesses such as diabetes, drug refractory epilepsy and chronic pain (Gregg, Callaghan, Hayes, & Glenn-Lawson, 2007;Lundgren, Dahl, Melin, & Kies, 2006;Wetherell et al, 2011). The focus of intervention involves working with adjustment issues related to acceptance of the chronic illness and focusing on living in the present moment rather than focusing on the illness symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This has primarily been used in clinical settings to aid in values clarification and committed action. A second measure is the Bull's-Eye, which assesses values attainment, discrepancy between stated values and behavior, perceived barriers to valued living, and behavioral persistence (Lundgren, Dahl, Melin, & Strosahl, 2008) and has been shown to function well as an outcome measure and a process measure and as a tool for educating clients about values in a clinical context (Lundgren, Dahl, & Hayes, 2008;Lundgren, Dahl, Kies, & Melin, 2006;Lundgren, Dahl, Yardi, & Melin, 2008). The Personal Values Questionnaire (Blackledge & Ciarrochi, 2006) is an ACT-consistent modification of Sheldon et al's (2002) Measures of values-consistent behavior have thus far been assessed by self-report in the clinical domain, through the use of values homework sheets, the consistency portion of the Valued Living Questionnaire, or the Bulls-Eye diary.…”
Section: Empirical Support For the Process Of Values In Actmentioning
confidence: 99%
“…Following a 9-hr values-focused ACT intervention for South Africans struggling with refractory epilepsy, Lundgren et al (2006) found that 57% of participants were completely seizure free at posttreatment (as opposed to none in the control group), and 86% were seizure free (as opposed to 8% in the control group) at a 1-year follow-up. Further, participants' level of values attainment and persistence in the face of barriers (as measured by the BullsEye) mediated improvements in frequency of seizures, overall well-being, and quality of life at a 1-year followup (Lundgren, Dahl, & Hayes, 2008).…”
Section: Empirical Support For the Process Of Values In Actmentioning
confidence: 99%